IMPROVING THE PEDAGOGICAL MECHANISM FOR DEVELOPING THE CREATIVE ABILITIES OF STUDENTS - Boymirzayeva Nafisaxon Bahodir qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article discusses the importance and specifics of collaborative learning in improving students ’creative abilities, which is one of the main criteria for determining modern professional skills.